2015
DOI: 10.13103/jfhs.2015.30.4.303
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Contamination in Kitchens and Refrigerators of Korea Households

Abstract: The objectives of this study were to investigate the microbial contamination level of domestic kitchen environments and to provide information to improve food safety in 50 domestic house kitchens located in Seoul, Incheon, and Gyeonggi-do. Dishcloth, chopping board, and refrigerator swabs were examined for the presence of coliforms, Salmonella spp., Campylobacter jejuni/coli, Escherichia coli, Listeria monocytogenes, and Staphylococcus aureus. The means and standard deviations of coliform counts for dishcloths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…Meat products such as beef and pork are potential sources of Campylobacter contamination [63]. Taremi et al (2006) found the highest prevalence of Campylobacter in [32,33,36,37,40,41,45,51,58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meat products such as beef and pork are potential sources of Campylobacter contamination [63]. Taremi et al (2006) found the highest prevalence of Campylobacter in [32,33,36,37,40,41,45,51,58].…”
Section: Discussionmentioning
confidence: 99%
“…Figure 4. Forest plot of prevalence of Campylobacter considering environmental factors and processing environments in South Korea: (A) feces, (B) equipment, (C) wash water[32,33,36,37,40,41,45,51,58].…”
mentioning
confidence: 99%